Keterampilan ibu rumah tangga dalam pemanfaatan limbah kain perca di Kecamatan Bontotiro Kabupaten Bulukumba - Nurlita Pertiwi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This program aims to increase housewives skill in inwaste management. This skill will improve the communityincome in Batang village of Bontotiro sub-district inBulukumba. The implementation of this program was carriedout in four stages, namely (1) identifying the potential waste atBatang village, (2) discuss with housewives about the potentialuse of waste, (3) training in the use of patchwork waste tomake accessories, (4) motivating housewives to innovate andfind other forms in using patchwork waste. The resultsobtained from these community service activities are (1)increasing motivation of housewives in managing patchworkwaste into economic goods, (2) improving the skills ofhousewives managing patchwork waste.